PERANCANGAN VIRTUAL REALITY TOUR SEBAGAI MEDIA INFORMASI TATA LETAK GEDUNG KAMPUS II IAIN BUKITINGGI - Anang Wijaya; Hari Antoni Musril; Riri Okra; Khairuddin Khairuddin (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2023)
The research was motivated by the problem of the number of students who did not recognize each campus building and sometimes some students were late for lectures because they did not know the location of the lecture hall. The method used is Research and Development (R&D). The development model applied by Luther Sutopo's that is Multimedia Development Life Cycle (MDLC) has 6 stages, the first is Concept, the second is Design, the third is Material Collection, the fourth is Assembly, the fifth is Testing, and the sixth is Distribution. The tests carried out in this study were product validity tests, product practicality tests, and product effectiveness tests. The results of the study are in the form of information media based on virtual reality tours as information media for IAIN Bukitinggi campus layout II that can be used by students wherever and whenever they have internet access